2011
DOI: 10.1007/s00247-011-2219-8
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular MRI without sedation or general anesthesia using a feed-and-sleep technique in neonates and infants

Abstract: Using this technique, infants younger than 6 months can complete a cardiovascular MRI without the need for sedation or general anesthesia. We advocate the incorporation of this safe and reliable technique into routine clinical practice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
59
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 104 publications
(61 citation statements)
references
References 5 publications
1
59
0
1
Order By: Relevance
“…Newer techniques enable infants <6 months of age to undergo a full study without anesthesia or sedation using the ''feed and swaddle'' technique. [90][91][92] Up to 15% of patients who have undergone the AtrSO have cardiac pacemakers; these devices as well as implantable defibrillators have historically been considered a contraindication to CMR. 93 However, research over the past decade has indicated that CMR in some patients with these devices may be reasonable and relatively safe under specific circumstances.…”
Section: Strengths and Limitationsmentioning
confidence: 99%
“…Newer techniques enable infants <6 months of age to undergo a full study without anesthesia or sedation using the ''feed and swaddle'' technique. [90][91][92] Up to 15% of patients who have undergone the AtrSO have cardiac pacemakers; these devices as well as implantable defibrillators have historically been considered a contraindication to CMR. 93 However, research over the past decade has indicated that CMR in some patients with these devices may be reasonable and relatively safe under specific circumstances.…”
Section: Strengths and Limitationsmentioning
confidence: 99%
“…The increased costs of MRI facilitated by anaesthesia are often favoured when compared with poor-quality MR images that result from infant movement. Some studies have documented high-quality MR images without any sedative3–15 and others have compared MRI without sedation with those with sedation 14 15. The studies examined the use of various methods of non-pharmacological sedation including earmuffs,4 8 13 14 feed and swaddle techniques,4 5 8 10–15 MR compatible pods5 11 12 and infant immobilisation devices 5 6 8.…”
Section: Commentarymentioning
confidence: 99%
“…The studies examined the use of various methods of non-pharmacological sedation including earmuffs,4 8 13 14 feed and swaddle techniques,4 5 8 10–15 MR compatible pods5 11 12 and infant immobilisation devices 5 6 8. The quality of the images was often assessed as being images free of motion artefact;3–5 7 9 10 other studies use ability to provide definitive diagnosis as quality criteria and8 14 15 still others define images as qualitatively appropriate based on radiologist evaluation 7 Table 1. includes those prospective studies that featured a sample size of at least 20 newborns or infants that met the above inclusion criteria.…”
Section: Commentarymentioning
confidence: 99%
“…Pero esta práctica supone la exposición del paciente a los riesgos asociados a la medicación sedante-anestésica, la disminución en la disponibilidad de la prueba, el aumento del coste sanitario y la necesidad de un tiempo de monitorización del paciente tras la prueba 1---3 . La posibilidad de llevar a cabo RM sin sedación-anestesia (RMSS) en el período neonatal aumenta tanto la seguridad del paciente como la disponibilidad y la rentabilidad de la prueba, lo que permite ampliar sus indicaciones 4,5 .…”
Section: Introductionunclassified